Full scale behavior of a small size vertical axis wind turbine. (November 2018) - Pagnini, Luisa; Piccardo, Giuseppe; Repetto, Maria Pia
Abstract: This paper shows the on-going experimental campaign carried out over a small size vertical axis wind turbine in the facility of the Savona Harbor. Investigations mainly concern two issues: power production assessment and full-scale structural behavior. The first one highlights the importance of a deep knowledge of the local orography and of the wind characteristics (e.g., turbulence intensity); in the absence of reliable wind data it is impossible to properly estimate the performance of the system. The latter allows to identify the possible critical aspects of the structural system (e.g., in terms of resonance conditions) and to investigate the actual dynamic behavior (e.g., in terms of dissipative capacity), necessary for assessing the useful life. The paper points out how these two issues are closely related. Results obtained can provide indications suitable for improving future installations. Highlights: Full-scale campaign on a small size vertical axis wind turbine. Investigation of wind field, energy production, structural behavior. Investigation of possible critical conditions. Extensive estimate of damping ratios in parked and operational conditions. Preliminary assessment of aerodynamic effects on structural behavior.